Developing “KUPANCAR”: A Guidebook and A Collection of Arabic-Speaking Host Texts to Enhance Students' Speaking Skills - Nuriyatul Hidayah; Muhaiban Muhaiban; Hanik Mahliatussikah; Nur Ain Hannani Binti Hamid (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2021)
Enhancing the skills of Arabic-speaking hosts in Indonesia is very important. This study aimed to describe the development process, the validity level, and the effectiveness of